DIPLOMASI KEBUDAYAAN JEPANG DI INDONESIA MELALUI THE JAPAN FOUNDATION TAHUN 2015-2018 - Evan Sares Pratama; Faisyal Rani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
This study aims to describe the development of the Japanese cultural sector which has undergone various policy changes since the Japanese era in building the empire, to the modern era where Japanese soft power is better known as 'cool japan'. Nowadays, the Japanese government is concerned about the cultural sector as well as military and economic interests.This research is theoretically built using a constructivist perspective, with the theory of public diplomacy. The formulation of all arguments, data, facts, and theoretical frameworks in this study uses a qualitative explanation method. This study also uses the nation-state as the level of analysis.This study aims to explain the form of Japanese cultural diplomacy carried out through The Japan Foundation. The Japan Foundation is an independent institution that is fully responsible for carrying out the objectives of Japanese cultural diplomacy overseas. The Japan Foundation has branch offices in various countries including Indonesia.Keywords : Japan Fouundation, culture, cool japan, soft power